Corrective Feedback on Sentence Structure Errors in Writing 4 Class - Kevin Susanto Pokhan (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study was done to find out the types of teacher’s corrective feedback and the errors in sentence structure that had teacher’s feedback on Writing 4A students’ first drafts of their four assignments. The writer used theories from Ellis (2009) about written corrective feedback and Ho (2005) about errors in sentence structure. This study was a qualitative study. The source of data was the Writing-4A’s four students’ first draft of their four assignments. The findings showed that the teacher used one type of corrective feedback: indirect corrective feedback to both groups with Electronic Feedback as the media for group B, and group B made more errors than group A did. Most of the errors were fragmented sentences, and happened when the students wrote compound sentences. In conclusion, the teacher did not differentiate the students in giving feedback, and B-students had more difficulties in creating compound sentences. Keywords: Feedback, Written Corrective Feedback, Errors in Sentence Structure